Det moderne menneskes situation og Grundtvigs antropologi - Michelsen, William (Grundtvig-studier, 1972)
The Situation of Modern Man and Grundtvig's Anthropology By William Michelsen The present essay purposes to set off Grundtvig’s view on man against a contemporary context - not least with regard to the categorical repudiation with which H. G. Ørsted, in 1814, and Georg Brandes, in 1872, met Grundtvig’s conception of history, but also considering a modern materialist philosophy. In both cases it is important to realise that Grundtvig’s conception of man (and history) did not follow the post-Kantian idealist philosophy. Moreover, the modem state of affairs differs from that of Grundtvig’s day in that modern science unlike Ørsted and his contemporaries does not claim that its explanation of the world is exhaustive. Further, attention is called to the difference between Grundtvig’s conception of man and history, and that proposed by Kant in his essays “ Idee zu einer allgemeinen Geschichte in weltbürgerlicher Absicht” (1784) and “ Muthmasslicher Anfang der Menschengeschichte” (1786). Grundtvig’s first sketches of an anthropology occur in a manuscript dated October 1813 “ On the Human Condition” (Værker i Udvalg I I , p. 240-70, cf. Nordisk Tidsskrift 1946). His first printed account occurs in his second Verdenskrønike (1814). The Connection between Grundtvig’s thought and the psychology of that time has been dealt with by Villiam Grønbæk; but we are still in need of an analysis of the ideas Grundtvig advanced in the journal Danne-Virke 1816-19, the contents of which he wrote himself, and in his third Verdenskrønike (1817). It is suggested that there is a close connection between these ideas and those proposed in the introduction to Nordens Mythologi 1832 and later, for instance in the hymns.